Nothofagus pumilio forest affected by recent tephra deposition in northern patagonia: II-shifts in diversity and structure of rhizosphere fungal communities - Fernández, Natalia V. (2018)
Volcanic eruptions have a significant effect on ecosystems, including soil and its fungal communities. Due to the eruption of the Puyehue-Cordón Caulle in 2011, thick tephra deposits accumulated in several Nothofagus pumilio forests in Northern Patagonia. The tephra deposition affected plant establishment and development during the post-eruption period. In this work we analyzed rhizosphere fungal communities associated with N. pumilio seedlings at three study sites sampled three years after the eruption, two with a thick tephra layer (50 cm) and a third site with no tephra deposition. Denaturing gradient gel electrophoresis (DGGE) was performed for the different fungal communities (Ascomycetes, Basidiomycetes and Total fungi). We found clear shifts in rhizosphere fungal communities, especially for Basidiomycetes and Total fungi. Site-related characteristics, such as type of substrate, light intensity and the existence of understory and previous mycelial networks, seemed to be the main factors determining the structure of these fungal communities. Given their sensitivity to different types of environmental change, these microbial communities could be used as bioindicators. Specifically, Basidiomycetes and total fungi seem to be better bioindicators of environmental changes than ascomycetes. The results shown here contribute to the understanding of how fungal communities respond to disturbance, an important issue in the evaluation of how ecosystem processes might be affected in areas commonly subjected to geological risks, such as volcanism. This information is also relevant to the planning and successful implementation of restoration activities based on seedling optimization by rhizosphere fungi.